Multi-agent financial market simulation: evolutionist approach. (1st January 2013) - Hedjazi, Badiâa; Ahmed-Nacer, Mohamed; Aknine, Samir; Benatchba, Karima
Financial markets are complex systems consisting of entities interacting and evolving in an uncertain environment. Their modelling and simulation requires the use on the one hand of a suited technology that is multi-agent systems (MASs) to model the various actors of a market, and on the other hand the evolutionary game theory to formalise interactions and heterogeneous investment strategies. The goal of this paper is to model, simulate and analyse financial markets dynamics. For this purpose, we propose three market models (fundamentalist, strategic, conventionalist) summarising various facets of real market speculation depending on the information held and the price formation process chosen by the investors. Each model is built using a multi-agent system. Moreover, investors' agents are modelled by classifier systems that are advanced structures to study their evolutionary and adaptive aspects.